2010
DOI: 10.5650/jos.59.247
|View full text |Cite
|
Sign up to set email alerts
|

Administration of DHA-PS to Aged Mice Was Suitable for Increasing Hippocampal PS and DHA Ratio

Abstract: Docosahexaenoic acid (DHA) and phosphatidylserine (PS) are major components of the brain and play important roles functionally and structurally. Aging is associated with impairments in biological functions. According to the results of animal tests it has been shown that the loss in brain PC, PS and DHA due to aging leads to a variety of nervous deficits. In the present study, young mice and aged mice were fed a test or control diet for four weeks, and the authors examined the effects of DHA and/or PS administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…PS derived from soy lecithin is currently given orally to adults at a dosage of 200–300 mg per day and to children at 520 mg per day. The substance has been tested in humans and animals at a higher dose than recommended for use in humans with no toxicity observed [42], [43], [44], [45]. The PS/DHA conjugate (Sharp·PS GOLD) increased the level of IKAP mRNA at much lower concentrations than the effective concentrations of PS in the FD cells used in our study.…”
Section: Discussionmentioning
confidence: 86%
“…PS derived from soy lecithin is currently given orally to adults at a dosage of 200–300 mg per day and to children at 520 mg per day. The substance has been tested in humans and animals at a higher dose than recommended for use in humans with no toxicity observed [42], [43], [44], [45]. The PS/DHA conjugate (Sharp·PS GOLD) increased the level of IKAP mRNA at much lower concentrations than the effective concentrations of PS in the FD cells used in our study.…”
Section: Discussionmentioning
confidence: 86%
“…Nevertheless, an increment in NAA concentration also induces many alterations such as oxidative stress, Canavan disease or genotoxicity and protein interaction due to an increase in nitric oxide produced by the elevated concentration of NAA (Surendran and Bhatnagar 2011 ). Compared with other organs, the brain has a high content of lipids, some two-thirds of which are phospholipids (Ohkubo and Tanaka 2010 ). Hippocampal pyramidal neurons represent by far the most abundant type of neuron in the hippocampus, and their dendritic arbor is covered by dendritic spines.…”
Section: Discussionmentioning
confidence: 99%
“…Liposomes prepared from natural lipid mixtures extracted from marine animals appeared to be superior candidates for DHA/EPA supplementation. The greater bioavailability of omega-3 PUFAs measured after phospholipid liposome ingestion, compared with triglycerides ingestion, is supported by a number of animal and clinical studies [57]. It has been also reported that decreases in brain plasmalogen phospholipids, one of the earliest biochemical changes detected in Alzheimer disease (AD), are specific to brain regions with AD pathology [8], and that the plasmalogen ether phospholipid precursors can be supplied by dietary supplements.…”
Section: Introductionmentioning
confidence: 99%